A agricultura e o desenvolvimento regional - Schuh, G Edward; Tollini, Hélio (Revista Ceres, 2025)
This paper makes two major points: (1) that the agricultural sector of the economy can make a positive contribution to the economic development of a country or region, and (2) that in orderto make its maximum contribution, it is necessary to make investiments in the rural sector in research and education. The first part of the paper discusses the changing role of agriculture in economic development. Inthis change, agriculture has movedfrom a neglected and ignored sector to one receiving major emphasis by development economists. The second part discusses the specific ways in which agriculture can contribute to economic development. This section is followed by a discussion of the techniques for making agriculture more productive, giving particular stress to a new conception of the production function. The final section consists of the implications of the model, in which specific recommendations are made. Major attention is given todeveloping successful research stations, graduate training centers, and the development of a sound educational system for rural areas.